The Effects of Light-to-Moderate Alcohol Consumption on the Cognitive Function of Community Nondemented Male Elderly: A Cohort Study - Zhang Yan; Zhang Yingjie; An Na; Qiu Qi; Li Wei; Wang Wenzheng; Sun Lin; Xiao Shifu (Behavioural Neurology)
Aim. To investigate the effects of light-to-moderate drinking on the cognitive function of the elderly in a large elderly community cohort. Although heavy drinking is linked with impaired brain functions, the effects of light-to-moderate drinking on the cognitive function of the elderly are still controversial. Methods. A total of 1469 nondemented elderly men from 15 research centers in 8 cities and provinces were included and divided into two groups: drinking (531 subjects) and nondrinking (938 subjects). Cognitive functions were assessed by the Beijing version of the Montreal Cognitive Assessment (MoCA) at baseline and one-year follow-up. Results. There was no difference in total cognitive scores between the light-to-moderate drinking and nondrinking groups at baseline and follow-up. Nonalcohol users performed better naming and abstraction function at baseline and better naming function at follow-up. There was no difference in cognitive performance decline and new-onset dementia rates at follow-up. Conclusions. Light-to-moderate alcohol consumption had no significant impact on the overall cognitive function and the risk of dementia in elderly men.